Dominasi Orang-Orang Besar Dalam Sejarah Indonesia: Kritik Politik Historiografi dan Politik Ingatan - Ganda Febri Kurniawan; W. Warto; Leo Agung Sutimin (Department of History, Faculty of Humanities, Diponegoro University, 2019)
This paper departs from the restlessness of some scientists about the dominant of the big man in Indonesia's historical narrative. It also becomes a form of public memory about the meaning of heroism which is more likely to be cultured rather than understanding academically. This article was composed an academic criticism of the conditions mentioned above, the political term historiography or historical writing that is used as a political interest is the most appropriate in describing Indonesia's current historiographic conditions. The dominance of the big man in history requires to be distorted and historiography needs to provide a place for stories of local heroes. Besides, memory politics also requires to be dammed through a counter-narrative that can be presented through critical historical studies, so that the desire to remember the forgotten will continue to live and become a guide for thinkers and activists of history.